Peran Mahasiswa KKN Dalam Pengembangan Pendidikan Anak-Anak di Desa Pintu Padang - Ihsan Batubara; Aini Fadilah Daulay; Resti Agustina; Melda Junita Nst; Nur Padilah; Cahyani Aulia Fitri; Khodijah Nasution; Siti Khairani (Institut Nalanda, 2024)
Student responsibilities in carrying out Real Work Lectures (KKN) to realize the Tri Dharma of Higher Education which is a component of service. This program aims to provide benefits to the surrounding environment. local people realize the value of education so they can support the government in educating the country's young generation. Devotion is realized through actions: additional tutoring for children, establishing a reading corner, teaching service learning, and teaching the Quran. This educational development activity provides understanding to the people of Pintu Padang village, Batang Onang sub-district, North Padang Lawas district about the concern of parents in teaching their children at home, not just at school, that children can read well, read books and the Quran, and provide understanding to teachers to carry out their duties in teaching school children.